Determinan Kemampuan Ibu Dalam Melakukan Deteksi Dini Tanda Bahaya Kehamilan - Rachmawati Ika Sukarsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: to identify Determinants Ability Of Pregnant Mothers Doing Early Detection Pregnancy Dangerous Signs. Methods: This article Uses a Descriptive Design To Determine The Determinants That Affect The Mother's Ability To Detect Early Pregnancy Danger Signs Results: Based on the characteristics of the respondents, the results obtained based on the age of 20-25 years as much as 25%, the level of education is mostly high school as much as 48.8%, work of housewives by 82.9%, domicile of own residence (nuclear family) by 52.%, Decision makers is husband by 51%.Based on the knowledge of the danger signs in pregnancy, the results obtained: knowing the danger signs of pregnancy 91.4%, the known danger signs of pregnancy is bleeding 65.7% Conclusion: The mother's ability to detect early pregnancy danger signs is closely related to the characteristics of pregnant women and the support from the pregnant mother's environment.